The Systematic, Intensive Instruction of Reading Comprehension Skills - Baumann, James F. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1984)
In direct instruction, the teacher, in a face-to-face, reasonably formal manner, tells, shows, models, demonstrates, and teaches the skill to be learned. Therefore, it is the teacher behavior aspect of classroom instruction that underpins the instructional strategy for teaching main ideas. Much has been learned about teacher behaviors that discriminate successful teachers from less successful teachers. Most of the teacher behaviors described in teacher effectiveness research cluster under the rubric "direct instruction." In a global sense, when direct instruction occurs, enough time is allocated to reading instruction, teachers accept responsibility for student achievement, and they expect that their students will learn. One direct instruction strategy for teaching students various reading comprehension skills is a five-step approach documented by the work and research of J. F. Baumann. The five steps consist of introduction, example, direct instruction, teacher directed application, and independent practice. That is, the teacher tells the students what the lesson will be about; the teacher provides an example; the teacher actually teaches the lesson; and then the teacher gradually releases responsibility for learning to the students through guided application exercises and by providing independent practice. (HOD)
ERIC Note: Paper presented at the Annual Meeting of the National Reading Conference (34th, St. Petersburg, FL, November 28-December 1, 1984).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Behavioral Objectives; Directed Reading Activity; Independent Study; Reading Comprehension; Reading Instruction; Reading Research; Reading Skills; Reading Strategies; Secondary Education; Teacher Behavior; Teacher Effectiveness; Teacher Role; Teaching Methods; Theory Practice Relationship; Direct Instruction; Speeches/Meeting Papers; Guides, Classroom -- Teacher